Assessing the Environmental Friendliness of Universitas Andalas for Stingless Bees Species (Hymenoptera: Apidae: Meliponini). Issue 1 (1st July 2022) - Herwina, H; Salmah, S; Mairawita,; Nurainas,; Jasmi,; Janra, M N; Sari, D A
Abstract: Stingless bees have become popular in the last six years because of their promising products such as honey, bee pollen, and propolis. A study on the stingless bees had been conducted in 2019 with the aim to see the ecological aspect dealing with the potency of stingless beekeeping (Meliponiculture) to be held within Universitas Andalas Campus Complex (UACC). A total of ten colonies from ten different stingless bee species were recorded from several sites in UACC and the condition of each colony was concisely observed. Plant species that presumably the potential food source for stingless bees were identified from selected sites at Herbarium, Arboretum, and Storage Spot. The uniqueness of every stingless bee colony and its potency in stingless beekeeping was discussed in this paper. A total of 66 plant species were recorded with note as possible sources for pollen, nectar or resin for stingless bee colonies.